PROSES BERPIKIR KREATIF SISWA DALAM MEMECAHKAN SOAL CERITA POKOK BAHASAN SPLDV BERDASARKAN TAHAPAN WALLAS DITINJAU DARI GAYA BELAJAR - Khasanah, Ulfatul; Sunardi, S; Sugiarti, Titik (Kadikma, 2018)
Abstract. The purpose of this research to describe the creative thinking process of students in solving SPLDV subject matter questions based on Wallas stages in terms of learning styles. The subjects of this study is class VIIIA students as many as 30 students at SMPN 1 Arjasa , then taken as many as 2 students from each learning style to analyze and conduct in-depth interviews. Data collection with learning style questionnaires, SPLDV test questions and interviews. The analysis of the results of tests and interviews shows that students who have a visual learning style can smooth the stages of creative thinking smoothly and can meet several indicators of creative thinking. Auditory learning style students can pass the stages of creative thinking smoothly, but students tend not to re-check the answers obtained. Auditory learning style students tend not to pass the stages of illumination and verification, students with kinesthetic learning styles cannot meet the indicators of creative thinking flexibility. The six subjects have not fulfilled the indicators of original creative thinking because they have not been able to produce new ideas that are different from other classmates based on their own thinking. Keywords: creative thinking process, Wallas stage, learning style.